A thematic analysis of Instagram's gendered memes on COVID-19. (2nd October 2021) - Al-Rawi, Ahmed; Siddiqi, Maliha; Li, Xiaosu; Vandan, Nimisha; Grepin, Karen
Abstract: We investigate the gendered use of Instagram memes on COVID-19 using a mixed-analysis approach. We find that memes referencing women are mostly related to community support and healthcare, which often express gratitude for frontline workers, while the majority of memes on men refer to news and promotion as well as suffering due to the high death rates and other financial hardships. As for sexual and gender minorities, memes mostly mention community support similar to the case of the memes referencing women. We argue that internet memes offer insight into ongoing trends in the public's perceptions of pandemics, and they should be further examined because they often communicate vital information on gender groups and public health.